TRADITIONAL GAMES AS A SOURCE OF CHARACTER VALUE FOR CHILDREN IN SIMOKERTO SURABAYA - Yoga Prasetya; SARMINI SARMINI (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe traditional games as a source of character values ​​for children in Simokerto Village, Surabaya. The focus of this study describes the mechanism of the Kampoeng Dolanan community in instilling character values ​​through traditional games of tug of war, stilts, and holahop in children and the integrated character values ​​in them. The research approach used is qualitative with a case study design, the subjects in this study are the head of the Kampoeng Dolanan community, members of the youth organization, children involved in traditional games in Simokerto Surabaya village and parents of children playing traditional games in Simokerto Surabaya village. The research location is in RT. 04 RW. 02 Simokerto Village, Surabaya City. Data collection techniques using interviews, and documentation. Data analysis using the model from Miles and Huberman through four stages of data collection, data reduction, data presentation, and drawing conclusions by juxtaposing the perspective of Ki Hajar Dewantara's 3N theory. The results show that the Kampoeng Dolanan community mechanism in instilling character values ​​through traditional games in children has three stages, namely introducing, playing, and preserving. The integrated character values ​​in the traditional tug of war game are courage, strength, cooperation and trust, the integrated character values ​​in the stilt game are courage, concern and cooperation, the integrated character values ​​in the holahop game are dexterity, balance, and hard work. Keywords: Traditional Games, Characters, Children..